Unpacking Impasse-Related Experience during Insight. (2019) - Shen, Wangbing; Yuan, Yuan; Lu, Fang; Liu, Chang; Luo, Jing; Zhou, Zhijin
Abstract: Mental impasse has long been recognized as a hallmark of creative insight, but its precise role has been unexplored. The aim of the present work, consisting of two studies, was to experimentally probe mental impasse perspective from insight experience, namely impasse-related experience during insight. In Study 1, participants were requested to complete a compound remote association task and a forced-choice subjective experience depiction task that could provide data on impasse-related experience. The results showed that reports of negative experience, such as feelings of loss ( t = –5.51, p < . 001, Cohen d = 1.07) and personal experience (mirrored by 'other' response; t = –2.62, p < . 05, Cohen d = 0.48), were more common in the impasse condition than in the no-impasse condition; correspondingly positive affect and positive cognitive experiences such as happiness ( t = 4.20, p < . 001, Cohen d = 0.77), ease ( t = 5.90, p < . 001, Cohen d = 1.20), certainty ( t = 7.46, p < . 001, Cohen d = 1.36) and calmness ( t = 4.42, p < . 001, Cohen d = 0.81) were experienced more frequently in the no-impasse condition. These findings were replicated in Study 2, in which participants were invited to solve a set of classic insight problems and to freely report any feelings of being at an impasse. Across two studies, this work suggests that impasse-related experience during insight problem solving is multi-faceted and consists of negative affective and cognitive components. The implications of these findings are discussed.